O fenômeno arquibancada: análise do afastamento das meninas nas aulas de Educação Física do Ensino Médio em uma escola na rede estadual de Minas Gerais - Carolina Mezzetti de Freitas Rochael (2020)
This study intends to understand what are the reasons and justifications that make students decide not to participate in Physical Education classes, which generates distance from classes. The research was carried out with a few teenagers from the 3rd and 2nd grades of High School in a public school in the State of Minas Gerais. The perspective of a qualitative, descriptive investigation was chosen, using notes in a research journal, interviews with the participants and two focus groups. Data analysis was developed from the perspective of Phenomenology that analyzes issues related to human experience, at a specific time and place. Therefore, the students' speeches were analyzed, categorized and interpreted in 3 categories defined as structural, pedagogical and behavioral, to present the possible reasons for the “bleachers” phenomenon present in the speech and behavior of the teenagers. In addition, to identify whether the bodily expectations imposed on female bodies influence the withdrawal from Physical Education classes. Finally, this study aims to deepen the debate on the theme of absence, discuss issues related to body and gender and enable reflections on interventions to motivate and include students in classes and Physical Education.